2023
DOI: 10.1088/1741-2552/acb9be
|View full text |Cite
|
Sign up to set email alerts
|

EEG-based detection of modality-specific visual and auditory sensory processing

Abstract: Objective. A passive brain-computer interface (pBCI) is a system that enhances a human-machine interaction by monitoring the mental state of the user and, based on this implicit information, making appropriate modifications to the interaction. Key to the development of such a system is the ability to reliably detect the mental state of interest via neural signals. Many different mental states have been investigated, including fatigue, attention and various emotions, however one of the most commonly studied sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 51 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Three types of baseline trials were collected: one in which passive stimuli in both modalities were presented at the higher speed, one in which the passive stimuli in both modalities were presented at the lower speed, and a true baseline in which the participant focused on the black computer screen with a constant '+' symbol in the center. Because the results of our previous work suggested that our BL L condition was too similar to the Aud L and Vis L conditions [28], we excluded them (and the BL H condition) and only the true baseline (BL) trials were considered in this work.…”
Section: Baseline Trialsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three types of baseline trials were collected: one in which passive stimuli in both modalities were presented at the higher speed, one in which the passive stimuli in both modalities were presented at the lower speed, and a true baseline in which the participant focused on the black computer screen with a constant '+' symbol in the center. Because the results of our previous work suggested that our BL L condition was too similar to the Aud L and Vis L conditions [28], we excluded them (and the BL H condition) and only the true baseline (BL) trials were considered in this work.…”
Section: Baseline Trialsmentioning
confidence: 99%
“…high or low). This was because our previous results suggested that level of demand could be classified with better accuracy than type of demand [28], and it is good practice in hierarchical classification to put more accurate layers first to avoid error propagation. It consisted of a single classifier trained using data from all task conditions.…”
Section: Classification 2431 Classification Problemsmentioning
confidence: 99%
See 2 more Smart Citations